The Role of Dayah Darul Mutaalimat Grong-Grong, Pidie District in Developing Santri - Ismail Ismail (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This research related to the leader's task in fostering dayah education is carried out using a qualitative approach, in order to obtain comprehensive information about the role of dayah leaders in fostering students in Darul Mutaalimat Dayah. The role of leadership in the development of dayah education is by fostering students. The purpose of this study is to analyze the role of the leader of the Dayah Darul Mutaalimat Grong-Grong in fostering students and to analyze various obstacles both internal and external in the process of fostering students. The theoretical implications obtained that Dayah Darul Mutaalimat Grong-Grong in Pidie Regency, the learning process is a local wisdom and this system is still maintained, preserved as a traditional education model. While the practical implications of the researchers recommend that there is a need for government policy and support in order to foster dayah education. The results showed that the leadership of Dayah Darul Mutaalimat Grong-Grong in Pidie Regency had a very large role in the development of students, ranging from determining the curriculum studied until the implementation process to achieve the vision and mission of developing students based on absolute provisions governed by dayah leaders. Then the dominant internal and external factors become supporters and inhibitors of the formation of students in Darul Mutaalimat Dayah, among others, related to teaching staff (teachers), the availability of adequate dayah facilities, and good management of management. Internal factors supporting the development of Darul Mutaalimat Dayah santri existence of teungku / teachers who teach do not demand hard work and they voluntarily want to foster students, the availability of adequate dayah facilities, the realization of good harmony among fellow teachers, good management of dayah management and the location of the dayah which is very representative. The internal inhibiting factors in the formation of Darul Mutaalimat Dayah students are related to the inability of the dayah to provide training facilities through IT equipment, the capacity of the dormitory is still very limited and also the status of the dayah still private. the administration of education which is the operational legal basis for fostering santri.